The Key to Achieving REDD+ Objectives - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Professor, Dr. Niels Elers Koch, President of IUFRO (International Union of Forest Research Organizations) highlights the importance of "Understanding Relationships between Biodiversity, Carbon, Forests and People: The Key to Achieving REDD+ Objectives" Report at #ALLForestDay, #COP18 in Doha, Qatar Video by Meerim Shakirova, social media reporter